Sustaining the Reading Current: Cognitive, Behavioral, and Emotional Engagement among Indonesian EFL University Students - Sinarman Jaya; Leffi Noviyenty (Universitas Hamzanwadi, 2026)
Reading engagement remains a critical concern in Indonesian EFL higher education, where students are required to engage with dense academic texts despite limited sustained reading practices. Although previous studies have examined reading motivation and strategies, less attention has been given to how cognitive, behavioral, and emotional engagement interact to sustain academic reading. This study investigated multidimensional reading engagement among Indonesian EFL university students through the lens of Directed Motivational Currents. A convergent mixed-methods design was employed, involving 110 third-semester students from four universities in Bengkulu, Indonesia, of whom 20 participated in semi-structured interviews. Quantitative data were analyzed using descriptive and correlational statistics, while qualitative data were examined through thematic analysis and integrated through triangulation. The findings revealed a high level of overall reading engagement, with emotional engagement emerging slightly higher than cognitive and behavioral engagement. Perceived progress in comprehension, alignment with future academic and professional goals, emotional satisfaction, and structured reading practices were identified as key factors supporting sustained engagement. Interview data further showed that students maintained engagement by segmenting complex texts, setting reading routines, monitoring comprehension, and connecting reading tasks to future-oriented goals. These findings suggest that EFL academic reading engagement is not driven by obligation alone but by the dynamic interaction of emotional reinforcement, goal-directed motivation, and strategic regulation. Pedagogically, EFL instructors should design reading activities that include explicit strategy training, manageable text segmentation, progress-based feedback, and goal-oriented scaffolding to sustain students’ engagement with academic texts.